The J Girls : a Reality Show - Hurt, Rochelle (Indiana University Press : Indiana Review, 2022)
Winner of the 2021 Blue Light Books Prize, Rochelle Hurt's The J Girls: A Reality Show is a tribute to the grit and glitter of millennial girlhood, a testament to its dangers and traumas, and an elegy for adolescent friendships.
Keywords: Female friendship -- Fiction.; Teenage girls -- Fiction.; Amitié féminine -- Romans, nouvelles, etc.; Adolescentes -- Romans, nouvelles, etc.; Women Authors.; Lesbian.; FICTION.; Coming of Age.; Screenplays.; PERFORMING ARTS.; Love & Erotica.; Subjects & Themes.; POETRY.; Female friendship; Teenage girls; Electronic books.; poetry.; Fiction; Poetry.; Fiction.; Poésie.; Romans.